Reductive activation of N2 using a calcium/potassium bimetallic system supported by an extremely bulky diamide ligand. Issue 91 (19th October 2022) - Mondal, Rahul; Yuvaraj, K.; Rajeshkumar, Thayalan; Maron, Laurent; Jones, Cameron
Abstract : Potassium reduction of a bulky diamido-calcium complex under an N2 atmosphere afforded the first well-defined, hetero-bimetallic s-block metal complex of activated dinitrogen. Abstract : An extremely bulky xanthene bridged diamide ligand ( TCHP NON = 4, 5-bis(2, 4, 6-tricyclohexylanilido)-2, 7-diethyl-9, 9-dimethyl-xanthene) has been developed and used to prepare two monomeric diamido-calcium complexes [( TCHP NON)Ca(D) n ] (D = THF, n = 2, 3; D = toluene, n = 1, 4). Reduction of 4 with 5% w/w K/KI under an N2 atmosphere gave the first well-defined, hetero-bimetallic s-block complex of activated dinitrogen, [K( TCHP NON)Ca2 (μ-η 2 :η 2 -N2 )] 5, presumably via a transient calcium(i ) intermediate.